Efecto bioestimulante ecofungi a base de micorrizas sobre la productividad del cultivo de maíz, INIAP 528, ESPAM 2007. - Vera Buste, Luis (2009)
In The Polytechnical Superior School of Farming of Manabi MFL located in Calceta, province of Manalof was realized the following investigation during the rain time of 2008, as a level of field as in laboratory. The objective was generate information as to influence of use "micorrizas" in the production of (corn) maize INIAP 528 in state of corncob. Seven treatments studied were: Inocululation seed 100 gr. /ha, Inocolulation to the seed 200 gr./ha, Inocolulation to the seed 300 gr./ha, Inoculation to the plant 100 gr./ha, Inoculation to the plat-if 200gr/ha, Inoculation to the plant 300 gr./ha., addition to a witnees the desing utilized was a full block in a Bifactorial addictive (TO XB+1),with 4 repeats. The data taken was the following. Height plants at 15, 30, 45 days, Height of insertion of cob, roots development, determination of percentage of colonization in roots of provide his data were analized statistically to the respective analysis of number of commercial corncob/ha, length of cob, diameter of cob, the (maize plant). This data were analyzed statistically by means of the respective analysis of variances (AAEVA), in that variables with statistical differences that were applied the Tukey test at 5% complementary was made an economic analysis. The result at field level determined that the treatment Inoculation to the seed 100 gr./ha obtained a yield of 45962 commercial corncob/ha. In the laboratory work was obtained the higest percentage of colonization in inoculated plants with the higest avantity 300g/ha, 50 the rain addition developing was found the differences. In the economic analysis that Represent a high greater was a treatment with the inoculation to the seed with the quantity 100 g/ha (ISAI)